The potential active compounds of Jatropha multifida Linn. as an anti-COVID-19 mouthwash: In silico study - Muhammad Chair Effendi; Aisyah Fitri Qurrata 'Ayun; Annisa Putri; Dhiky Dwi Kurniawan; Dinda Aprilla Salsabila; Fahrunisa Tunjung Malihahsisna (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Povidone-iodine 1% mouthwash is one of the products recommended for preventing and controlling COVID-19 infection in dental procedures. Jatropha multifida Linn. has the same antiseptic effect as povidone-iodine. Purpose: The objective is to determine the effectiveness and interaction effect of secondary metabolites from the latex of Jatropha multifida Linn. and povidone-iodine against the main protease (MPro) SARS-CoV-2 and the SARS-CoV-2 spike protein - ACE2 receptors. Methods: The in silico test was used in this study and carried out using the Molegro Virtual Docker software for molecular docking and BIOVIA Discovery Studio and PyMOL for visualization. Results: The results show that secondary metabolite compounds contained in the latex of Jatropha multifida Linn. have a better effectiveness potential in relation to MPro SARS-CoV-2 and SARS-CoV-2 spike protein - ACE2 receptors than povidone-iodine. Conclusion: The latex of Jatropha multifida Linn. shows potential as a preventive and curative therapy for COVID-19 in the in silico study.